Aplikasi Biofertilizer Pelarut Silika Berformulasi Dietanolamida Olein Sawit pada Berbagai Dosis NPK untuk Mendukung Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Suria Paloh; Nurmayulis Nurmayulis; Abdul Hasyim Sodiq; Fitria Riany Eris (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2026)
Cocoa (Theobroma cacao L.) is one of the commodities with high economic value and contributes to Indonesia's foreign exchange through the food, beverage, and pharmaceutical industries. This study evaluated the application of silicate-solubilizing biofertilizer formulated with palm olein diethanolamide at different NPK rates on the growth of cocoa seedlings. The experiment employed a factorial randomized block design with two factors. The first factor consisted of three silicate-solubilizing biofertilizer formulations enriched with palm olein diethanolamide biosurfactant, namely coffee rhizosphere, oil palm rhizosphere, and microbial consortium. The second factor was NPK 16:16:16 rate at 100%, 90%, and 80% of the recommended dose. The experiment comprised 9 treatment combinations with 3 replications, resulting in 27 experimental units and 54 cocoa seedlings. Observed variables included plant height, leaf number, stem diameter, and leaf greenness. The results showed that biofertilizer application significantly affected cocoa seedling growth. The consortium formulation produced the best response for most growth parameters. The 80% NPK rate also showed favorable results, and its combination with the consortium formulation produced the highest response in several variables. These findings indicate that silicate-solubilizing biofertilizer formulated with palm olein diethanolamide has the potential to improve cocoa seedling growth while supporting NPK fertilizer efficiency through a 20% dose reduction during the nursery stage.